Assessment of DNA Ploidy in Oral Potentially Malignant Disorders Using a VELscope - Pushpanjali Das; Revati Shailesh Deshukh (Journal of Clinical and Diagnostic Research, 2023)
Introduction: The device VELscope (Visually enhanced lesion scope) is intended as an aid to the clinician to complement a conventional white light exam (whether it be a general oral cavity examination or examination of a particular lesion) to detect abnormal tissue that might have otherwise been overlooked. In this study, it was used concomitantly with ploidy status to evaluate the malignancy potential of Oral Potentially Malignant Disorders (OPMD). Aim: To evaluate potential of Deoxyribonucleic Acid (DNA) ploidy as a preliminary adjunct to oral biopsy to identify patients with aneuploidy for the necessity of biopsy, and to assess the sensitivity of VELscope in the determination of accurate clinical parameters of the lesions in the oral mucosa. Materials and Methods: This in-vivo cross-sectional study was carried out in Department of Oral and Maxillofacial Pathology and Oral Microbiology, Bharati Vidyapeeth Deemed to be University, Pune from February 2020 to February 2021. Clinically diagnosed OPMD were included in the study, after verification of clinical extension boundaries by VELscope. DNA ploidy status was evaluated with DNA image cytometry and exclusive individuals with aneuploidy were biopsied followed by histopathological evaluation and surgical removal of the lesion. One way Analysis of Variance (ANOVA) test was used to compare the mean in 4 study groups [Oral leukoplakia, Oral submucous fibrosis, Oral lichen planus and Tobacco pouch keratosis] vs control. Sensitivity, specificity, positive predictive value and negative positive value was calculated by using the ROC (Receiver Operating Characteristic Curve) analysis. A p-value <0.05 was considered as significant for evaluating sensitivity of VELscope and evaluation of ploidy status. Results: The study included patients whose mean age was 45.8 years. The groups had tobacco habits in one of the various forms [smoke or smokeless] both in experimental and control group. VELscope could identify the clinical borders of the OPMDs considered via the loss of autofluorescence. Lesion borders were identified precisely with the loss of autofluorescence. It was quite helpful especially in aneuploid cases where the whole margin could be removed leaving no genetically aberrant cells behind. Oral submucous fibrosis was concluded to have maximal sensitivity of 86.7%, 100% in specificity and positive predictive and 88.2% negative predictive value. Conclusion: DNA ploidy could decipher the malignancy potential and could identify the individuals who needed biopsy. VELscope was able to mark the clinical diameters which were not visible to naked eyes clinically. Oral submucous fibrosis was found to be group with the maximum potential of malignancy followed by Oral Lichen Planus, Oral Leukoplakia and Tobacco Pouch Keratosis.